A Study of CEFR Level B1 Vocabularies On Instagram - Ratini Setyowati; Beta Setiawati; Desi Rohma Khurniawati (LPPM Universitas Duta Bangsa Surakarta, 2022)
Language competence is needed in this era because in this revolution industry 4.0 foreign companies can built their business in Indonesia. Therefore, as Indonesian generation must be ready to face this international competition using international languages. The purpose of the study is to Improve CEFR Level B1 Vocabularies Through Instagram. Research design used in this research was qualitative research. Literature study is carried out to obtain the necessary data by reading the literature sources. The data was collected from some English Instagram accounts in August 2022, the accounts are Bahasa Inggris Daily, Belajar_Bahasa.Inggris, Kampunginggrislc, bahasainggris, Englishtoday.bali, the result of this study is the accounts post some vocabulary, phrases/idioms for improving English skills by proving some information about proper vocabularies, synonym and how to apply them. Through Instagram, English learners can improve their vocabularies although not every account post English vocabularies that related to CEFR Level B1 Vocabularies. Conclusion of the study is Instagram can facilitates English Learners to improve their English skill.